Upper incisor angular movement and its correlation to the hard and soft tissues in Malay bimaxillary protrusion cases with transpalatal arch reinforcement / Naili Hayati Abdul Mukti - Abdul Mukti, Naili Hayati (2018)
Introduction: Bimaxillary protrusion is characterized by increased proclination of upper and lower incisors with either prognathic maxilla and mandible or normal skeletal pattern and protrusive upper and lower lip. Bimaxillary protrusion presents in most ethnic group in the world and predominant in Asian countries and also in African population. In some patient, this condition really affects their profile and patient often seek treatment to improve their facial appearance. This research is based on data obtained from Postgraduate Clinic UiTM Sungai Buloh and Puncak Perdana. Aim of the study: The aims of this study were to analyse incisor angular movement and its correlation with the changes of the underlying hard and soft tissues in bimaxillary protrusion in Malay cases with transpalatal arch. Material and Methods: Thirteen female subjects with bimaxillary protrusion were recruited in this study with extraction of upper first premolars extraction and reinforced anchorage transpalatal arch. Pre-treatment and near end lateral cephalometric radiographs were taken to evaluate the hard and soft tissues changes.